THE EFFECT OF PROVIDING FERMENTED WATER EXTRACT OF PAPAYA LEAVES (Carica papaya L.) THROUGH DRINKING WATER ON THE OF ABDOMINAL FAT IN KUB CHICKENS - N.K.C., Agustina; Siti, N. W.; Nuriyasa, I M. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
High levels of abdominal fat in chickens are considered detrimental to the carcass quality of KUB chickens. The aim of this study was to determine the effect of administering fermented papaya leaf water extract through drinking water on abdominal fat levels in 8 week old KUB chickens. The treatments tested included providing drinking water without the addition of papaya leaf water extract, as well as adding papaya leaf water extract to drinking water with percentages of 2% (Treatment B), 4% (Treatment C), and 6% (Treatment D), respectively. Rations were given ad dlibitum and drinking water was given every 2 hours. Variables observed included the percentage of fat pads, mesentery, gizzards, and abdomen. This research shows that the addition of papaya leaf water extract at a concentration of 4% and 6% significantly reduces the percentage of abdominal fat. From these findings, it is concluded that the addition of papaya leaf water extract at levels of 4% and 6% through drinking water is effective in reducing abdominal fat levels in KUB chickens.